Pengaruh Pengetahuan Kewirausahaan, Motivasi Berwirausaha dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa - Arisma Lusia Nur Shanty; Waspodo Tjipto Subroto (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the effect of entrepreneurial knowledge, entrepreneurial motivation and family environment on student entrepreneurial interest. The research method is causal associative with a quantitative approach. The population used is students of PE, PAK, PAP, and PTN Study Programs at the Faculty of Economics and Business, Surabaya State University class of 2019 totaling 214 students. Sampling using convenience sampling technique amounted to 139 students. Sampling using convenience sampling technique of 139 students. The data analysis technique used is multiple linear regression analysis and classical assumption test with the help of the SPSS Version 25 for Windows program. The results showed entrepreneurial knowledge, entrepreneurial motivation and family environment partially and simultaneously affect the interest in entrepreneurship, with the contribution of the magnitude of the influence of 58.8%. Conclusion, the influence of entrepreneurial knowledge, entrepreneurial motivation and family environment on student entrepreneurial interest. Keywords: Entrepreneurial Interest, Entrepreneurial Knowledge, Entrepreneurial Motivation, Family Environment